Role of Social Media as Historical Marketing Tool for Heritage Sites in Eastern New York State - Pepe, Michael S.; Bournique , Rachel (Contemporary Research in Business, Management and Economics Vol. 1, 2024)
New York State has a rich history of heritage tourism dating back to 1836 with the establishment of the State Geological and Natural History Survey, now known as the New York State Museum. Marketing activities are becoming more integrated into the areas of public history, museum studies, and heritage tourism to enhance the long-term success of each. Heritage tourism marketing has been studied around the globe with many different areas of focus. This study examines heritage site marketing techniques in New York State and uses three research objectives: (1) to determine what marketing techniques are currently being used by heritage sites (2) to examine how the heritage sites use social media and (3) to determine social media best practices for heritage sites and recommendations for improvement. A survey was developed consisting of four parts with a possible total of 24 questions and was designed based on previous research about survey development, the literature review and primarily to achieve the research objectives. The survey was completed by a total of 53 participants. Based on the literature review and results of the survey, social media is growing in use and importance for heritage sites. Websites and Facebook are currently being used by heritage sites and these two are found to be the most effective types of social media. Findings show that New York State heritage sites primarily use word-of-mouth marketing, relationship marketing, and e-marketing. Social media is used to communicate mostly with adults and seniors but does not focus heavily on millennials which is a major issue as identified in the study. Finally, the preferred social media platforms used by heritage sites are websites and Facebook, which are effective tools for visitor engagement, marketing events, programs and exhibits, and attracting new visitors.